INTELECTUAIS E EDUCAÇÃO INFANTIL NO BRASIL (1994-1998) - Moletta, Ana Keli (2012)
This dissertation discusses the actions of intellectuals involved in the debate about the Brazilian Early Childhood Education in the period between 1994 and 1998. In specific terms,it debates the intellectual interventions at three moments of the history of the Early Childhood Education: Coedi/MEC (1994-1997), Coedi/MEC (1997-1998) and Anped. Under the coordination of Angela Maria Rabelo Ferreira Barreto (1994-1997), the intellectuals developed a set of seven “notebooks” that aimed at assisting the organization of a national policy for Early Childhood Education. However, this group did not accomplish the organization of a single document for the Early Childhood Education (referential), which was one of the reasons why it was removed from the MEC (Ministry of Education and Culture),even though it had a widely recognized cultural capital in the field of the Early Childhood Education. In contrast, the group led by Gisela Wajskop (1997-1998) complied with the model of public politics divulged by the MEC, organizing the National Curriculum Referential for the Early Childhood Education (Rcnei). The Rcnei had a strong impact among intellectuals related to the Early Childhood Education, especially among members of the group linked to the GT7 of the Anped, motivating them to step forward and question the official truth presented by the Ministry of Education. The actions of intellectuals in the MEC are discussed in the light of the works of Pierre Bourdieu, particularly of the two-dimensional intellectual concept, which allows us to state that the disputes faced by the two groups are typical of the two-dimensional condition of the intellectual that, while possessing a cultural capital, participates in the political filed, which has rules of its own and, therefore, differs from the standards of the scientific field. As for the interventions of the GT7 group, we seek to understand them by resorting to Michel Foucault's concept of critical intellectual and to Bourdieu's concept of collective intellectual, sustaining that the intellectuals' role is to refuse to accept certain impositions by means of manifestos, petitions and the medias to make public their concerns and demand actions in their field of competence. The participation of the intellectuals in the discussion regarding the Early Childhood Education was shaped by the social spaces they occupied, either in the MEC and/or the Anped. These roles distinguished the peculiarities of their functions, since, when joining the MEC, they were involved with the determination to articulate pedagogical ideas and the demand for elaboration of public politics, while, when returning to the academic field (and especially when regarding their strategies from inside the Anped), they had assumed the role of criticizing the results of the Rcnei. Therefore, the richness of the relation between intellectuals and politics is inscribed in the heat of the great struggles, a determining factor that has motivated us to investigate the dialectic between the developers of educational thought and political organizers.